Laparoscopic resection of recurrent ectopic hepatocellular carcinoma: A case report with review of the literature and guidelines for follow-up - Aarås, Arne Marino (Int J Surg Case Rep, 2015)
INTRODUCTION: Hepatocellular carcinoma (HCC) in ectopic liver tissue is extremely rare. PRESENTATION OF CASE: A 64-year-old woman presented initially with abdominal complaints. Computed tomography (CT) revealed a tumor in the diaphragm and laparoscopic resection of the tumor was performed. Histology showed HCC. During the next 4 years four more tumors, all of which showed HCC on histology and were located extrahepatically, was treated with laparoscopic resection. During this course the patient was followed with regular thoracoabdominal CT and measurement of serum alpha-fetoprotein (AFP). A negative magnetic resonance imaging (MRI) examination of the liver excluded a primary intrahepatic tumor. DISCUSSION: The literature available on ectopic HCC and the guidelines for management of HCC do not address the postoperative surveillance of patients undergoing curative treatment. A follow-up regime has been proposed by Hatzaras et al. (2014) to include cross-sectional imaging of the liver and measurement of serum AFP levels [1]. CT would be the preferred study of choice in a total radiologic investigation of the abdomen. While MRI is prone to artifacts due to movements, CT scans allows so rapid recordings that this no longer is an issue. An early investigation of the liver for intrahepatic HCC should nevertheless be performed early to exclude primary intrahepatic HCC. CONCLUSION: We recommend that patients with ectopic HCC should be followed every 6 months with measurement of AFP and abdominal CT imaging. MRI of the liver should be performed early to exclude primary intrahepatic HCC.